Abortion care in women with underlying medical conditions: The role of multidisciplinary team approach in increasing safety of abortion procedures - Abraham Fessehaye Sium; Sarah Prager; Ferid A. Abubeker; Lucero‐Prisno Don Eliseo III; Wondimu Gudu (Wiley, 2023)
Abstract Background There are no clear data driving most clinical recommendations for abortion care in women with underlying medical conditions, such as cardiac disease. Current abortion practice in such women is based on limited retrospective studies, mainly case reports and case series. In our institution (a tertiary center in Ethiopia), we practice a multidisciplinary team approach to abortion care for patients with medical conditions. Objective Describe the value of a multidisciplinary team approach in abortion care in patients with underlying medical conditions. Methods This is a retrospective descriptive analysis of abortion care in women with underlying medical conditions (cardiac and noncardiac medical conditions) over a 5‐year period (November 2016-October 2021) at St. Paul's Hospital Millennium Medical College, in Ethiopia. Data were extracted by reviewing patients' medical records using a structured questionnaire. Simple descriptive statistics were applied for analysis using SPSS version 23. Results are presented as frequencies and percentages. Results Fifteen induced abortion cases in women with underlying medical conditions were analyzed, out of which 11 were in women who were critically ill. The median gestational age was 20 weeks. Ten subjects, 10/15 (66.7%), had a cardiac condition, whereas the rest 5/15 (33.3%) were noncardiac cases. Ten out of the 11 critically ill patients were managed under multidisciplinary team approach, and there were no complications encountered. Out of these, 7/10 (70%) received medication abortion care between 19 and 25 weeks gestation, including 5 cardiac patients with New York Heart Association‐III and IV conditions. Conclusion In this study, more than three quarters of women with medical conditions who had abortion care were critically ill, and almost all of them were managed with a multidisciplinary team approach. None of the patients suffered a deterioration of their medical conditions, demonstrating the utility of incorporating a multidisciplinary team approach during abortion care for such cases.